1940
DOI: 10.6028/jres.025.013
|View full text |Cite
|
Sign up to set email alerts
|

Combination of wool protein with acid and base: The effect of temperature on the titration curve

Abstract: Equilibrium measurements are reported of the amounts of hydrochloric acid and potassium hydroxide bound by wool, as a function of pH and salt concentration at 0°, 25°, and 50° C. In order to eliminate from the measurements of base combination effects due to decomposition, a study was also m ade of the effect of temperature on the rate of decomposition of the disulfide bonds in wool and on the rate of solution of the fiber in alkaline solutions. The data support the assumption made in accounting for previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1941
1941
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…+ an a~+ K'{; (5) This equation differs from eq 3 only by the presence of a correction term which affects appreciably only the upper part of the curve. This low-affinity form (eq 3), rather than the high-affinity form, is required because when salt is present the amounts of acid bound should be almost wholly given by the sum of the terms [WHAj and [WH+j.…”
Section: Data Obtained In the Presence Of Saltmentioning
confidence: 94%
See 2 more Smart Citations
“…+ an a~+ K'{; (5) This equation differs from eq 3 only by the presence of a correction term which affects appreciably only the upper part of the curve. This low-affinity form (eq 3), rather than the high-affinity form, is required because when salt is present the amounts of acid bound should be almost wholly given by the sum of the terms [WHAj and [WH+j.…”
Section: Data Obtained In the Presence Of Saltmentioning
confidence: 94%
“…The curves in this figure represent the theoretical relations which are obtained when values of KA', shown in figure 1 for a number of acids selected to cover a wide range of affinity, and the value of Kg' at 0°0 previously established [3,5] are inserted in eq 4. The logarithmic ordinate has been chosen because it yields approximation to a linear relation to pH [3], and furnishes a more critical visual criterion of fit than a linear ordinate allows.…”
Section: Experimental Justification Of the Modified Equations 1mentioning
confidence: 99%
See 1 more Smart Citation
“…, " : " , The solutions were kept at 50 0 ±0.1° 0 for from 3 to ·5 days, periods which have been shown in earlier work [5,7] to be sufficient, for a close approach to equilibrium. T~e following measnr:ements were ~hen made on aliquots OT each; (a) pH' at roonl temperature; (b).…”
Section: Methodsmentioning
confidence: 99%
“…The alkaline branches of the curves are less dissimilar and, in this case, at least, a part of the difference may be attributed to a t('mperature effect. It has been shown that temperature appreciably influences the binding of base by wool but has very little effect on the binding of acid [11].…”
Section: Harrismentioning
confidence: 99%